Design of a Four-Branch Optical Power Splitter Based on Gallium-Nitride Using Rectangular Waveguide Coupling for Telecommunication Links - Retno W. Purnamaningsih; Nji R. Poespawati; Elhadj Dogheche (Journal of Engineering)
This paper reports design of a simple four-branch optical power splitter using five parallel rectangular waveguides coupling in a gallium-nitride (GaN) semiconductor/sapphire for telecommunication links. The optimisation was conducted using the 3D FD-BPM method for long wavelength optical communication. The result shows that, at propagation length of 925 μm, the optical power input was successfully split into four uniform output beams, each with 24% of total input power. It is also shown that the relative output power distribution is almost stable through the C-band range. At the operating wavelength of 1.55 μm, the proposed power splitter has an excess loss lower than 0.2 dB. This study demonstrates the opportunity to develop optical interconnections from UV-Visible to near IR wavelengths.